2020
DOI: 10.21037/tlcr-19-477
|View full text |Cite
|
Sign up to set email alerts
|

Predicting brain metastasis in early stage non-small cell lung cancer patients by gene expression profiling

Abstract: Background: Non-small cell lung cancer (NSCLC) is the most common cause of cancer-death due to early metastatic spread, in many cases primarily to the brain. Organ-specific pattern of spread of disease might be driven by the activity of a specific signaling pathway within the primary tumors. We aimed to identify an expression signature of genes and the relevant signaling associated with the development of brain metastasis (BM) after surgical resection of NSCLC.Methods: Rapidly frozen NSCLC surgical specimens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Risk factors for BM in NSCLC reported previously comprise: Age(9)(10)(11), gender (11), non-squamous cell carcinoma/ adenocarcinoma(9)(12)(13)(11), clinical stage (13), number of extracranial metastases(10), malignant pleural effusion(10), nodal involvement (12), EGFRm or ALKr(13)( 14), high CEA(8), neutrophil-lymphocyte ratio (15), elevated neuro-speci c enolase (9),and high CA125 (9), with the exception of the latest two, all were analyzed in the present study. Although several clinical markers have been explored, no adequate model has a proven capability of predicting which patients with NSCLC will have BM (5) or failing to identify a group who would bene t from prophylactic cranial irradiation as a measure of extending overall survival (16), there is a window of opportunity exploring molecular markers (7). Previous authors have de ned a high-risk group for BM according to particular characteristics, to mention some: a) Age < 70 years, adenocarcinoma or large cell histology, tumor size > 3 cm, tumor grade ≥ II, and node positive disease(6), b) Adenocarcinoma, EGFRm + or ALKr + and CEA > 20 pg/mL (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for BM in NSCLC reported previously comprise: Age(9)(10)(11), gender (11), non-squamous cell carcinoma/ adenocarcinoma(9)(12)(13)(11), clinical stage (13), number of extracranial metastases(10), malignant pleural effusion(10), nodal involvement (12), EGFRm or ALKr(13)( 14), high CEA(8), neutrophil-lymphocyte ratio (15), elevated neuro-speci c enolase (9),and high CA125 (9), with the exception of the latest two, all were analyzed in the present study. Although several clinical markers have been explored, no adequate model has a proven capability of predicting which patients with NSCLC will have BM (5) or failing to identify a group who would bene t from prophylactic cranial irradiation as a measure of extending overall survival (16), there is a window of opportunity exploring molecular markers (7). Previous authors have de ned a high-risk group for BM according to particular characteristics, to mention some: a) Age < 70 years, adenocarcinoma or large cell histology, tumor size > 3 cm, tumor grade ≥ II, and node positive disease(6), b) Adenocarcinoma, EGFRm + or ALKr + and CEA > 20 pg/mL (8).…”
Section: Discussionmentioning
confidence: 99%
“…Predictor variables had to be either studied or present in at least 10% of the studied population for inclusion in the model. Missing data occurred in tumor grade (15%), tumor size (18%), CEA (58%) and NLR (52%), imputation of such large amount of missing data was considered unreliable, and the missing values were included in a separate category as previously done (6); therefore, regarding parameters missing for some of the cohort, statistical tests were calculated for the available data similar to previous reports (7), after these adjustments, complete information used for analysis is reported for 277 patients in the TD and 293 patients in the VD.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this, we predict that the physical features define largely the types of metastasizing cells can go through the BBBs to reach the internal parts of a brain and the enzymes may define the characteristics of primary cancer cells that survive and thrive in the brain microenvironment. Compared with published studies on prediction of brain metastasis for primary tumors, our model shows higher or comparable accuracy ( 56 , 57 ), but has two key superiorities: (i) the features used in our model are strongly supported by published studies and provide strong information about the key mechanisms of brain metastasis; and (ii) the primary locations of BMPs are not limited to one organ instead any organs, strongly suggesting that our predicted mechanism captures something fundamental.…”
Section: Resultsmentioning
confidence: 58%
“…Nonetheless, it identified few crucial genes which might lead to BrM development. Kamer et al discovered a similarly indicated signature for lung cancer, which additionally predicted metastatic spread with and without brain involvement [ 29 ]. The genes involved metastatic spread to the brain from the lungs were mainly oxidative phosphorylation pathway genes, indicating that perhaps in BrM, a more efficient way of utilising glucose which is highly available in this microenvironment is necessary to meet the demands of the rapidly growing metastasis.…”
Section: Biomarkers For Prognostication and Differential Diagnosis Of...mentioning
confidence: 99%